Strategi Kampanye Eko Hendro Purnomo di Media Sosial Instagram dalam Kemenangan Pemilihan Legislatif 2024 - Renyu, Andre Fransisco; Pasha, Julian Aldrin (Innovative: Journal Of Social Science Research, 2025)
Legislative elections have become an activity that is always held every five years, especially in Indonesia. With so many candidates for legislative members competing with each other, of course the people's choice is someone who is able to communicate himself well. So, they have more fame and power than other prospective members. However, with the existence of KPU Regulation No. 15 of 2018 concerning restrictions on campaign props, many legislative candidate members use alternative methods in campaigning. In this study, we will write about the influence of Political Communication using Social Media, especially Instagram as one of Eko Hendro Purnomo's campaign strategies in winning the 2024 Legislative Election. By explaining the concept of messages via Social Media, this article concludes that the success of a political campaign requires planning. and forming a suitable team to maximize the campaign strategy.